Assessment of proteins and lipids consumption by bodybuilders young men with a tendency to muscle dysmorphia (Research, Society and Development, 2021)
Muscle dysmorphia (MD), also denominated bigorexia or the Adonis Complex, is a form of body dysmorphic disorder that mainly affects teenagers and young men who believe that their body structure is too small and insufficiently muscular. The purpose of this work was to identify among bodybuilders registered in two gyms in the metropolitan region of Belo Horizonte, Minas Gerais, young men with a tendency to MD, and assess their daily consumption of proteins and lipids. The sample was composed of 30 men from 18 to 45 years old, bodybuilders for at least one year, with a minimum frequency of three times a week. To identify which participants presented a tendency to MD, an Adonis Complex Questionnaire was filled in. The assessment of the food consumption was made through the 24-hour food memory, in which was included the food supplement ingested by the interviewed. 63.3% of the participants presented mild to moderate tendency to MD, and 6.7% demonstrated elevated tendency. 76.2% of the interviewed with a tendency to MD consumed hyper protein diets, and 85.7% hypo lipidic diets. Regarding the food supplement consumption, 71.4% of the participants with a tendency to the disorder were using these substances, of which 46.7% did not have nutritional guidance. The importance of nutritionists with MD familiarity was reinforced to precociously identify among their patients the tendency to develop the disorder, making it possible the definition of the best methods of nutritional therapeutic approach.